Pengembangan Media Pembelajaran Ke NWDI-An Berbasis Mobile - Putra, Yupi Kuspandi; Muh. Adrian Juniarta Hidayat; Fathurrahman; Almi Yulistia Alwanda; Ahmad Firdaus (Fakultas Teknik Universitas Hamzanwadi, 2025)
The rapid development of information and communication technology (ICT) has brought significant changes in various aspects of life, including in the field of education. The need for effective and efficient learning media is increasingly urgent along with demands to improve the quality of education that is relevant to current developments. However, there are still several obstacles such as the lack of active role of students in the learning process and the limited learning media used. Learning resources in presenting material still use PowerPoint slides which are not yet interactive, resulting in a lack of student interest in learning. Therefore, this research aims to develop learning media, to support a more effective and interactive teaching and learning process. The method used in this research is Research and Development with the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation) which is a teaching design system that is centered on individual learning, has immediate and long-term phases, is systematic, and uses a systems approach to knowledge. and human learning. The result of this research is a mobile-based learning media application with the hope that it can help increase students' understanding and interest in learning in NWDI courses, especially at the Faculty of Engineering, Hamzanwadi University.